(untitled) (International journal of artificial intelligence, 2024)
This article explores models and strategies for achieving "green growth" in developing countries. By integrating sustainable development goals (SDGs) with economic policies, the article highlights pathways to balance economic growth with environmental protection. Key emphasis is placed on the role of renewable energy, eco-friendly technologies, and sustainable urbanization in fostering green growth. The article provides a comprehensive analysis of case studies and theoretical frameworks, offering actionable recommendations for policymakers and stakeholders.